Democracia participativa e experimentalismo democrático em tempos sombrios1 - Gaspardo, Murilo [UNESP] (Instituto de Estudos Avançados da Universidade de São Paulo, 2018)
The debate about the legitimacy crisis of representative democracy has gained new contours in the face of the somber times that characterize contemporary national and international politics. Thus, proposals for changes in the party-electoral system are common and, among progressives, the defense of more radical reforms based on the participatory democracy model. Although this model remains relevant at the normative level, there are strong indications that it has its lost political strength. Based on these premises, we review the construction of this model as an alternative to the liberal-elitist one, its main characteristics and the difficulties to achieve its objectives. Then, taking the idea of democratic experimentalism as a reference, we try to lay out some perspectives for innovations in participatory institutions that help us to confront the intellectual and political prostration in which we live.

O debate a propósito da crise de legitimidade da democracia representativa ganhou novos contornos diante dos tempos sombrios que caracterizam a política nacional e internacional contemporânea. Diante disso, são comuns propostas de mudanças no sistema partidário-eleitoral e, no campo progressista, a defesa de reformas mais radicais a partir do modelo de democracia participativa. Embora no âmbito normativo tal modelo conserve sua relevância, há fortes indícios de que perdeu força política. A partir dessas premissas, revisitamos a construção desse modelo como alternativa ao liberal-elitista, suas principais características e dificuldades de concretização de seus objetivos. Em seguida, tomando como referência a ideia de experimentalismo democrático, procuramos traçar algumas perspectivas para inovações nas instituições participativas que nos ajudem a enfrentar a prostração intelectual e política em que vivemos.
Keywords: Participatory democracy; Democratic experimentalism; Legitimacy; Institutional innovations; Democracia participativa; Experimentalismo democrático; Legitimidade; Inovação institucional